2018
DOI: 10.1016/j.omtm.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding of Macaque Hematopoietic Stem and Progenitor Cells: A Robust Platform to Assess Vector Genotoxicity

Abstract: Gene therapies using integrating retrovirus vectors to modify hematopoietic stem and progenitor cells have shown great promise for the treatment of immune system and hematologic diseases. However, activation of proto-oncogenes via insertional mutagenesis has resulted in the development of leukemia. We have utilized cellular bar coding to investigate the impact of different vector designs on the clonal behavior of hematopoietic stem and progenitor cells (HSPCs) during in vivo expansion, as a quantitative surrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Importantly, IS can also provide evidence of potential concerning integration patterns in tumorsuppressor genes, like PTEN 6 , TET2 7 and NF1 8 , which can be closely monitored during long-term follow-up to predict future severe adverse events. Genetic barcoding on the DNA level has been used to track the in vitro 9 and in vivo [10][11][12][13] clonal dynamics of heterogeneous mammalian cellular populations and offers several advantages over lentiviral IS tracking, although it has not been used clinically. First, the amplified region is known and nearly the same for each barcode simplifying recovery from targeted cells, as opposed to semi-random LV integrations, which require amplification of unknown sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, IS can also provide evidence of potential concerning integration patterns in tumorsuppressor genes, like PTEN 6 , TET2 7 and NF1 8 , which can be closely monitored during long-term follow-up to predict future severe adverse events. Genetic barcoding on the DNA level has been used to track the in vitro 9 and in vivo [10][11][12][13] clonal dynamics of heterogeneous mammalian cellular populations and offers several advantages over lentiviral IS tracking, although it has not been used clinically. First, the amplified region is known and nearly the same for each barcode simplifying recovery from targeted cells, as opposed to semi-random LV integrations, which require amplification of unknown sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Nonhuman primate transplantation studies offer a valuable preclinical bridge for this, due to their closer phylogenetic proximity to humans compared with mice and zebrafish. 67,68 Early work tracking the cell cycle status of baboon HSPCs indicated these cells are extremely quiescent, consistent with the murine lineage tracing studies demonstrating minimal activity of HSCs during steady-state hematopoiesis. 69 Using rhesus macaque autologous transplantation with lentiviral cellular barcoding, the Dunbar lab demonstrated that contributions from short-term HSCs and uni-lineage engrafting progenitors disappeared by 2-3 months post-transplantation, while long-term HSC contributions persisted with similar clonal dynamics beyond 3 months.…”
Section: Fundamental Insights Into Hspc Biology and Function From Mmentioning
confidence: 54%
“…While hematopoiesis is highly conserved in vertebrate and mammalian models, a challenge remains to translate the significance of mouse and zebrafish findings into human HSCT practice. Nonhuman primate transplantation studies offer a valuable preclinical bridge for this, due to their closer phylogenetic proximity to humans compared with mice and zebrafish 67,68 . Early work tracking the cell cycle status of baboon HSPCs indicated these cells are extremely quiescent, consistent with the murine lineage tracing studies demonstrating minimal activity of HSCs during steady‐state hematopoiesis 69 .…”
Section: Fundamental Insights Into Hspc Biology and Function From Manmentioning
confidence: 84%
See 1 more Smart Citation
“…Beyond the scope of this review, retrieval of IS has been critical to understanding the genotoxic events linked to activation of proto‐oncogenes via integration of clinical gene therapy vectors 78,79 . Modelling the likelihood of such events via quantitative clone tracking in animal models, via detection of pre‐malignant clonal expansions, is an approach to predict genotoxicity of new vectors prior to clinical introduction 80,81 . In addition, clonal tracking can be used to understand the impact of ex vivo expansion on HSPC function or numbers, or associate engraftment with particular phenotypic classes of HSPCs 28 …”
Section: Insights Into Clinically Relevant Aspects Of Haematopoiesis mentioning
confidence: 99%